PELATIHAN PEMBUATAN WEBSITE TANPA CODING DENGAN MEMANFAATKAN CONTENT MANAGEMENT SYSTEM WORDPRESS UNTUK UMUM DAN MAHASISWA KAMPUS MDP - Ahmad Farisi; Anggoro Aryo P; Mulyati (LP3K Lampung, 2021)
Website is a provider for delivering information that can be accessed online. Website creation can be conducted in various ways. Some ways to create a website are writing program code through a series of programming with web programming languages, using a content management system (CMS), and using a website builder. CMS is a method used to create websites for those who are not familiar with programming. One of the widely used CMS is WordPress. Currently 30% of websites in the world use WordPress and WordPress has dominated 60% of CMS users worldwide such as Joomla, Drupal, Magento and Shopify. This Wordpress training are carried out live and online via the MDP TV YouTube channel. This activity begins by conducting a survey of the needs from the training participants, followed by administrative preparations, the creation of training materials and questionnaires, conducted online and started with filling out the pre-training questionnaire, and ending with a post-training evaluation questionnaire. Based on the training and the results of questionnaires that have been filled out by 57 participants, the training went smoothly and received a very good response and was in accordance with the expectations of the participants.